SPIRITUAL DISCIPLINE OF PRAYER - Watopa, James Jonah (Klabat Theological Review, 2025)
Prayer is an essential communication that relates to transcendence. Every religion in the world must practice prayer in their religious life. For this reason, this study seeks to explore how important prayer is for every religious believer. In this study, the method used is document research or library research. The discussion is based on some legitimate literature to support this issue. For Christianity, prayer is the breath or opening of contrite hearts to God. This discussion discusses explicitly Jesus' prayer in John 17, which consists of prayer for Himself, His disciples, and all believers. Furthermore, prayer brings all the burdens and purposes of life to God, who is trusted to provide solutions in the form of answers. Although the answer is not by personal request, it is with faith, believing it is God's answer. Those who pray diligently and unceasingly are proof of the faithfulness of their faith. For this reason, prayer is a must element for every religious believer, especially in Christianity. Keywords: Prayer, Jesus’ prayer, unceasing, faithfulness, transformation and forgiveness